2004
DOI: 10.1097/01.md.0000145367.17934.75
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Sarcoidosis

Abstract: This retrospective study concerned 18 female and 23 male patients with cardiac sarcoidosis (CS). The average age at CS diagnosis was 38 years. CS was observed in white (73% of cases) and in black or Caribbean patients (27% of cases). All patients had extracardiac histologic proof of sarcoid tissue. In 63% of cases, the CS arose during the follow-up of systemic sarcoidosis. Systemic sarcoidosis was not specific except for a high frequency of neurosarcoidosis. Revealing cardiac signs were clinical in 63% of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(60 citation statements)
references
References 99 publications
0
53
1
6
Order By: Relevance
“…Small‐sized retrospective studies showed that steroid improved nearly 50% of cardiac sarcoidosis patients with complete AV block 2, 3. Chapelon‐Abric et al demonstrated that clinical response to prednisolone was limited to the early stage of cardiac sarcoidosis 6. In addition, other studies suggested that steroid was less effective in cardiac sarcoidosis patients with severe left ventricular dysfunction 7…”
Section: Discussionmentioning
confidence: 99%
“…Small‐sized retrospective studies showed that steroid improved nearly 50% of cardiac sarcoidosis patients with complete AV block 2, 3. Chapelon‐Abric et al demonstrated that clinical response to prednisolone was limited to the early stage of cardiac sarcoidosis 6. In addition, other studies suggested that steroid was less effective in cardiac sarcoidosis patients with severe left ventricular dysfunction 7…”
Section: Discussionmentioning
confidence: 99%
“…15 ChapelonAbric et al also reported that 87% of CS patients who received corticosteroid therapy had clinical improvement, although the study population was relatively small. 5 Furthermore, several case reports have documented the effectiveness of corticosteroid therapy for improving LV function, atrial arrhythmias, advanced AV block, and electrocardiographic abnormalities in CS patients, even in those with severe myocardial damage. 8-12, 18 The present study examined clinical outcomes of CS patients for a longer follow-up period and grouped patients into treated and untreated groups at the diagnosis of CS, rather than identifying untreated patients on post-mortem diagnosis.…”
Section: Effect Of Corticosteroid Therapy On Long-term Clinical Outcomementioning
confidence: 99%
“…1 Cardiac involvement is diagnosed antemortem in approximately 5% of systemic sarcoidosis patients but is seen in up to 25% of patients with systemic sarcoidosis on autopsy. 2 The leading causes of death in patients with sarcoidosis are cardiac arrhythmias, progressive heart failure, and progressive respiratory failure.…”
Section: Introductionmentioning
confidence: 99%